After revision anterior cruciate ligament reconstruction, who returns to sport? A systematic review and meta-analysis. Issue 20 (10th June 2015) - Grassi, Alberto; Zaffagnini, Stefano; Marcheggiani Muccioli, Giulio Maria; Neri, Maria Pia; Della Villa, Stefano; Marcacci, Maurilio
Abstract : Background: Return to sport and to pre-injury level represents an important outcome after both primary and revision anterior cruciate ligament (ACL) reconstructions. Purpose: The aim of the present meta-analysis was to determine the return to sport rate after revision ACL reconstruction. Material and methods: A systematic search was performed of the MEDLINE, Embase and the Cochrane Central Register of Controlled Trials Databases. All the studies that reported return to sport, return to pre-injury sport level and return to high level/competitive sport was considered for the meta-analysis. The overall pooled mean of post-operative knee laxity and pooled rate of positive pivot-shift and objective International Knee Documentation Committee (IKDC) categories was calculated as well. Results: Overall, 472 abstracts were identified and screened for inclusion and only 16 studies reported the rate of return to any level of sport activity at the final follow-up of 4.7 years (range 1.0–13.2 years), showing a pooled rate of 85.3% (CI 79.7 to 90.2). The return to pre-injury sport level was achieved in 53.4% (CI 37.8 to 68.7) of cases. Normal or quasi-normal objective IKDC, less than 5 mm of side-to-side difference at arthrometric evaluations and grade I-II pivot-shift test were reported in 84%, 88% and 93% patients, respectively. Conclusions: In spite of almost 8 patients out of 10 returning to sport after revision ACL reconstruction and showing good stability, only half of the patients returned to the same pre-injury sport level.